Molecular Regulation of Circadian Chromatin - Zhu, Qiaoqiao; Belden, William J. (Journal of molecular biology, 2020)
Circadian rhythms are generated by transcriptional negative feedback loops and require histone modifications and chromatin remodeling to ensure appropriate timing and amplitude of clock gene expression. Circadian modifications to histones are important for transcriptional initiation and feedback inhibition serving as signaling platform for chromatin-remodeling enzymes. Current models indicate circadian-regulated facultative heterochromatin (CRFH) is a conserved mechanism at clock genes in Neurospora, Drosophila, and mice. CRFH consists of antiphasic rhythms in activating and repressive modifications generating chromatin states that cycle between transcriptionally permissive and nonpermissive. There are rhythms in histone H3 lysine 9 and 27 acetylation (H3K9ac and H3K27ac) and histone H3 lysine 4 methylation (H3K4me) during activation; while deacetylation, histone H3 lysine 9 methylation (H3K9me) and heterochromatin protein 1 (HP1) are hallmarks of repression. ATP-dependent chromatin-remodeling enzymes control accessibility, nucleosome positioning/occupancy, and nuclear organization. In Neurospora, the rhythm in facultative heterochromatin is mediated by the frequency (frq) natural antisense transcript (NAT) qrf. While in mammals, histone deacetylases (HDACs), histone H3 lysine 9 methyltransferase (KMT1/SUV39), and components of nucleosome remodeling and deacetylase (NuRD) are part of the nuclear PERIOD complex (PER complex). Genomics efforts have found relationships among rhythmic chromatin modifications at clock-controlled genes (ccg) revealing circadian control of genome-wide chromatin states. There are also circadian clock-regulated lncRNAs with an emerging function that includes assisting in chromatin dynamics. In this review, we explore the connections between circadian clock, chromatin remodeling, lncRNAs, and CRFH and how these impact rhythmicity, amplitude, period, and phase of circadian clock genes. A subset of mechanisms involved in circadian clock regulation with a focus on chromatin-associate events. The schematic depicts generalized factors required for proper circadian clock function that are the subject of this review. (RNA, The red solid line; DNA, black solid line; nucleosomes, gray cylinders). [Display omitted] •Chromatin modifications and chromatin remodeling are integral to circadian clock transcription.•Circadian chromatin involves cycles of activating and repression modifications.•Circadian regulated facultative heterochromatin involves deacetylation, histone H3 lysine 9 methylation, and HP1binding.•Changes to genome structure occur over the circadian cycle.•Age-related changes to circadian output likely occur because of changes to circadian chromatin.